Preservasi Koleksi Buku Langka di Perpustakaan "X" - Aulia, Fadila; Rachman, Yeni Budi (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2023)
The “X” library is a special library that manages rare books collection, especially those published by Balai Pustaka. This study aims to determine the activities carried out by the "X" library in managing and preserving rare books collection published by Balai Pustaka. This research is qualitative research with a case study method. The data were collected by observation, interviews, and document analysis. The selection of research informants was carried out using a purposive sampling technique. The results indicated that the "X" Library has been conducting two components of physical preservation activities to its rare book collections, namely preventive conservation and passive conservation.